2010
DOI: 10.1038/eye.2010.110
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the management of TB-associated uveitis

Abstract: Aim The aim of this study is to highlight the pitfalls in the diagnosis and management of tuberculosis (TB)-associated uveitis. Methods This is a retrospective review of case records of four patients with TB-associated uveitis. Results In cases 1 and 2, failure to treat tubercular uveitis with anti-tubercular therapy (ATT) and unopposed steroid therapy led to a serious systemic consequenceFdevelopment of intra-cranial tuberculoma. In case 4, similar failure to initiate ATT caused recurrent disease (focal choro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…In our series, intraocular inflammation resolved without recurrence in all patients treated in this way. Although corticosteroid or immunosuppressive therapy may cause a re-activation of systemic TB resulting in severe disseminated TB and even a panophthalmitis, 4,26 we suggest that the presence of certain sight-losing complications, such as cystoid macular edema, or severe intraocular inflammation, justifies the use of corticosteroid treatment under the coverage of ATT. The route of administration of corticosteroids may be topical, periocular, or systemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, intraocular inflammation resolved without recurrence in all patients treated in this way. Although corticosteroid or immunosuppressive therapy may cause a re-activation of systemic TB resulting in severe disseminated TB and even a panophthalmitis, 4,26 we suggest that the presence of certain sight-losing complications, such as cystoid macular edema, or severe intraocular inflammation, justifies the use of corticosteroid treatment under the coverage of ATT. The route of administration of corticosteroids may be topical, periocular, or systemic.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical reactions in the eye such as worsening of the inflammation or existing lesions, or appearance of new lesions have also been described. 26,27 However, we feel that standard full 6 months ATT is generally justified to minimize the risk of ocular damage. In our series, intraocular inflammation resolved without recurrence in all patients treated in this way.…”
Section: Discussionmentioning
confidence: 99%
“…10 Paradoxical worsening in ocular TB has been described both in immunocompromised and immunocompetent patients. 5,[11][12][13] We have earlier described four cases of paradoxical worsening in the eye, two of which occurred following ATT for extra-ocular TB. 13 Gupta et al 5 reported 12 patients with SLC (14% of 84 patients in the study), who developed progressive inflammation following initiation of ATT.…”
Section: Site Of Progressive Inflammationmentioning
confidence: 99%
“…3 Moreover, administering corticosteroid or immunosuppressive therapy for severe intraocular inflammation without the coverage of ATT may cause re-activation of systemic TB, resulting in severe disseminating TB or even panophthamlitis. 4,5 In a large series of patients with presumed intraocular TB and latent TB combination treatment with corticosteroids and ATT reduced the risk of developing recurrence of the uveitis by approximately two-thirds compared to Correspondence treatment with corticosteroids alone. 6 Based on the above and on the results of our study, we stated that a minimum of 6 months standard ATT is generally justified in patients with presumed intraocular TB and latent TB.…”
Section: Sir Reply To Wakefield and Kumarmentioning
confidence: 99%